Prevalence and distribution of triticeal cartilage - Emre, E.; Akkoc, R. F.; Ogeturk, M. (Via Medica, 2022)
Background: The triticeal cartilage can be found in the lateral thyrohyoid ligament. The triticeal cartilage may exist in different shapes and locations, may be present unilaterally or bilaterally, or absent. The study aims to determine the prevalence, distribution, level, shape, and the degree of ossification of the triticeal cartilage by using three-dimensional computed tomography angiography (CTA). Materials and methods: Computed tomography angiography images of 1450 patients (785 women and 665 men), obtained in the period from 1 January 2017 to 30 September 2019, were evaluated retrospectively. Any unilateral or bilateral presence or the absence of triticeal cartilage was recorded with its anatomical level, shape, and degree of ossification. Results: At least one triticeal cartilage was found in the CTA images of 57.4% (833 out of 1450) patients. The prevalence was 51.3% in women (403 out of 785) and 64.7% in men (430 out of 665). Bilateral triticeal cartilages were more common compared to unilateral ones. Ossification was most commonly mild at a rate of 39.1%. A round-shaped triticeal cartilage was the most common form at a rate of 46.6%. Triticeal cartilage was detected at various intervertebral disc levels from the second and third cervical vertebrae to the level of the sixth cervical vertebra. Conclusions: Triticeal cartilage is common in the Turkish population and it should receive substantial attention from clinicians because it can be confused with calcified plaques and fractures of the superior horn of the thyroid cartilage. Therefore, for appropriate diagnoses and treatment, it is important to know the prevalence of triticeal cartilage with its distribution, intervertebral disc levels of location, shapes, and ossification degrees. (Folia Morphol 2022; 81, 1: 150-156)
Keywords: triticeal cartilage; computed tomography angiography; thyrohyoid complex; triticeal ossification